Un chico valiente como yo - Wilhelm, Hans. (Barcelona, Spain : Editorial Juventud, 1992)
A young boy who is "cool" on the outside has some inner fears that he expresses to his grandmother.
Translation of: A cool kid--like me!
Keywords: Self-confidence -- Fiction; Grandmothers -- Fiction